Intra-axonal Ca2+ mobilization contributes to triphenyltin-induced facilitation in glycinergic transmission of rat spinal neurons. (March 2019) - Noma, Kazuki; Kurauchi, Yuki; Katsuki, Hiroshi; Oyama, Yasuo; Akaike, Norio
Abstract: Triphenyltin (TPT) is an organotin compound causing environmental hazard to many wild creatures. Our previous findings show that TPT increases of the frequency of spontaneous glycinergic inhibitory postsynaptic currents (sIPSCs) in rat spinal neurons without changing the amplitude and 1/e decay time. In our study, the effects of 2-aminoethoxydiphenyl borate (2-APB), dantrolene sodium, and thapsigargin on sIPSC frequency were examined to reveal the contribution of intra-axonal Ca 2+ mobilization by adding TPT. 2-APB considerably attenuated the TPT-induced facilitation of sIPSC frequency while dantrolene almost completely masked the TPT effects, suggesting that the TPT-induced synaptic facilitation results from the activation of both IP3 and ryanodine receptors on endoplasmic reticulum (ER) membrane, though inositol triphosphate (IP3 ) receptor is less sensitive to TPT. Thapsigargin itself significantly increased the sIPSC frequency without affecting the current amplitude and decay time. Successive addition of TPT could not further increase the sIPSC frequency in the presence of thapsigargin, indicating that thapsigargin completely masked the facilitatory action of TPT. Results suggest that TPT activates the IP3 and ryanodine receptors while TPT inhibits the Ca 2+ -pump of ER membranes, resulting in the elevation of intra-axonal Ca 2+ levels, leading to the increase of spontaneous glycine release from synaptic vesicles. Highlights: TPT increased the frequency of spontaneous glycinergic postsynaptic currents (sIPSC). 2-APB (IP3 receptor inhibitor) decreased the sIPSC frequency facilitated by TPT. Dantrolene (ryanodine receptor inhibitor) masked the TPT-induced facilitation. Thapsigargin (ER Ca 2+ -pump inhibitor) was more potent than dantrolene. TPT is concluded to mobilize intra-axonal Ca 2+, resulting in the facilitation of sIPSC.